2015
DOI: 10.1038/ki.2014.306
|View full text |Cite
|
Sign up to set email alerts
|

Burnt sugarcane harvesting is associated with acute renal dysfunction

Abstract: Sugarcane harvesting has been associated with an epidemic of chronic kidney disease in Central America mainly affecting previously healthy young workers. Repeated episodes of acute kidney dysfunction are hypothesized to be one of the possible mechanisms for this phenomenon. Therefore, this exploratory study aimed to assess the acute effects of burnt sugarcane harvesting on renal function among 28 healthy non-African Brazilian workers. Urine and blood samples were collected at the beginning and at the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 37 publications
5
67
2
6
Order By: Relevance
“…Previous studies among sugarcane cutters in Brazil, El Salvador and Nicaragua have also observed similar changes in hydration and kidney function biomarkers that have been attributed to heat stress (8,11,13). Some of the workers in this study met the criteria for AKI over the course of a working day as reported among Brazilian cane cutters (11).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Previous studies among sugarcane cutters in Brazil, El Salvador and Nicaragua have also observed similar changes in hydration and kidney function biomarkers that have been attributed to heat stress (8,11,13). Some of the workers in this study met the criteria for AKI over the course of a working day as reported among Brazilian cane cutters (11).…”
Section: Discussionsupporting
confidence: 79%
“…Some of the workers in this study met the criteria for AKI over the course of a working day as reported among Brazilian cane cutters (11). In this study, these negative changes were related to the individual's production, a finding not previously reported.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations